(untitled) (International Journal of Engineering and Computer Science, 2017)
Mapping Twitter conversations on maps over time has become a well-liked means of visualising conversations around events on Twitter. giant events are the topic of most of those kinds of visualizations, wherever the speed of geo-tagged tweets is high enough to create attention-grabbing visualizations over the chosen time period. However, within the case of smaller events, or smaller countries wherever the frequency of tweets generated for events is lower, we tend to area unit naturally long-faced with an occasional variety of geo-tagged tweets, that makes it uninteresting to use these information for mapping and visualisations. This paper demonstrates application of Twiloc - a tweet location detection system - for mapping the voice communication around associate degree EU Qualifiers match between eire and Scotland. The paper more presents atiny low comparison between the results obtained from Twiloc and CartoDB Twitter Maps for national capital Marathon tweet dataset. Twiloc uses varied options for deciding the situation of each single tweet it receives, leading to a considerably higher rate of tweets with associated location data, and thence allows tweet location analysis and image for smaller events.